The progress and promise for metal–organic framework-mediated synthesis of lithium-ion battery cathode materials - Lianfen Chen; Jiafan Fang; Jiexun Lin; Minying Zhao; Yiqing Liu; Jian-En Zhou; Yongbo Wu; Xiaoming Lin (Materials Futures)
The growing dependence on lithium-ion batteries (LIBs) requires the advancement of electrode materials, where cathode technology is a pivotal factor for the overall electrochemical performance. To overcome the inherent limitations (i.e. structural vulnerability, limited capacity, sluggish ion/electron transport, poor environmental endurance) of conventional LIB cathodes, it is necessary to execute multiscale modification to improve key parameters like specific capacity, electrical/ion conductivity, cell voltage, cycling stability, and power/energy density, which can be realized by template-assisted synthetic methods. As typical porous crystalline materials, metal–organic frameworks (MOFs) remain promising self-sacrificial templates for the directional fabrication of LIB cathodes owing to their structural/compositional adjustability and affluent electrochemical active sites. In this context, the MOF-mediated synthetic method has attained much attention in the multidimensional modification of different LIB cathodes. Here, this paper begins with the categorization of prevailing LIB cathode materials based on their structures and working mechanisms. The following section introduces the MOF-mediated synthesis method and highlights its advantages in contrast to the conventional synthetic route. Afterward, the electrochemical properties of various MOF-derived LIB cathodes are evaluated and compared to embody their structure–activity correlation. Last, the outlook on the challenges and potential future development directions of MOF-derived LIB cathodes is provided to direct the LIB technology innovation.